Comparative Genome Analysis Reveals Cis-Regulatory Elements on Gene-Sized Chromosomes of Ciliated Protists - Zheng, Weibo; Dou, Huan; Li, Chao; Al-Farraj, Saleh A.; Byerly, Adam; Stover, Naomi A.; Song, Weibo; Chen, Xiao; Li, Lifang (Frontiers in Microbiology, 2022)
Gene-sized chromosomes are a distinct feature of the macronuclear genome in ciliated protists known as spirotrichs. These nanochromosomes are often only several kilobase pairs long and contain a coding region for a single gene. However, the ways in which transcription is regulated on nanochromosomes is still largely unknown. Here, we generated macronuclear genome assemblies for two species of Pseudokeronopsis ciliates to better understand transcription regulation on gene-sized chromosomes. We searched within the short subtelomeric regions for potential cis-regulatory elements and identified distinct AT-rich sequences conserved in both species, at both the 5’ and 3’ end of each gene. We further acquired transcriptomic data for these species, which showed the 5’ cis-regulatory element is associated with active gene expression. Gene family evolution analysis suggests nanochromosomes originated in spirotrichs more than 900 million years ago, and gene families that play a role in transcription factor binding and sequence-specific DNA binding rapidly expanded in both P. carnea and P. flava. Together our comparative genomic analyses reveal novel insights into the biological roles of cis-regulatory elements on gene-sized chromosomes.